2011
DOI: 10.1021/jp111977q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diffusivity Data Derived from Electrochemical and NMR Investigations of the SeCN¯/(SeCN)2/(SeCN)3¯ System in Ionic Liquids

Abstract: Electrochemical studies in room temperature ionic liquids are often hampered by their relatively high viscosity. However, in some circumstances, fast exchange between participating electroactive species has provided beneficial enhancement of charge transport. The iodide (I¯)/iodine (I(2))/triiodide (I(3)¯) redox system that introduces exchange via the I¯ + I(2) ⇌ I(3)¯ process is a well documented example because it is used as a redox mediator in dye-sensitized solar cells. To provide enhanced understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…ILs BmimNTf 2 , (99%), HmimNTf 2 (99%), and DmimNTf 2 (99%) were purchased from IoLiTec. 1-Butyl/hexyl/decyl-3-methylimidazolium selenocyanate (Bmim/Hmim/Dmim SeCN) was synthesized according to a previously described method, 73 and the contents of residual potassium ions (8.9 ppm in Bmim SeCN, 21 ppm in Hmim SeCN, and 15 ppm in Dmim SeCN) in the ILs were measured using ICP−MS. Ethanol (200-Proof, 99.5%), toluene (99.9%), and methanol (extra dry, 99.8%) were from Fisher Chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…ILs BmimNTf 2 , (99%), HmimNTf 2 (99%), and DmimNTf 2 (99%) were purchased from IoLiTec. 1-Butyl/hexyl/decyl-3-methylimidazolium selenocyanate (Bmim/Hmim/Dmim SeCN) was synthesized according to a previously described method, 73 and the contents of residual potassium ions (8.9 ppm in Bmim SeCN, 21 ppm in Hmim SeCN, and 15 ppm in Dmim SeCN) in the ILs were measured using ICP−MS. Ethanol (200-Proof, 99.5%), toluene (99.9%), and methanol (extra dry, 99.8%) were from Fisher Chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…The observed ν(CN) stretching frequencies for both Se 2 (CN) 2 and Se(SeCN) 2 were reported as being at 2144 cm −1 . We therefore speculate from this previous literature evidence that the peak could be due to an (NCSe) 3 − species, because this species is thermodynamically favored when in equilibrium with its progenitor species (SeCN) 2 and NCSe − , according to Solangi et al 51 In the presence of K + ion (from the use of KSeCN), the (SeCN) 3 − ion may precipitate and become "trapped" in this form as a K(SeCN) 3 film on the electrode. This compound is known from earlier studies 9 involving the oxidation of selenocyanate on platinum electrodes in aqueous electrolytes containing 0.5 mol L −1 KSeCN and 0.1 mol L −1 NH 4 O 2 CMe at pH 7 and was attributed to an intense band at 2143 cm −1 that was observed when applied potentials >0.8 V (NHE) were used.…”
Section: Ir Spectra Of Cu/tbap/ncsementioning
confidence: 76%
“…In addition, the CV of NH 4 SCN shows two oxidation processes between 0.7 and 1.7 V and a reduction process at 0.25 V, which correspond to the pseudohalide system of {SCN−(SCN) 3 −(SCN) 2 } (Figure S4). 18 On the basis of the control experiments and CV studies, a plausible mechanism was proposed, as shown in Scheme 5.…”
Section: Scheme 2 Electrochemical C−h Phosphorothiolation Of Imidazo-...mentioning
confidence: 99%